De novo design of potent inhibitors of clostridial family toxins - Robert J. Ragotte; Huazhu Liang; John Tam; Sean Miletic; Jacob M. Berman; Roger Palou; Connor Weidle; Zhijie Li; Matthias Glögl; Greg L. Beilhartz; Kenneth D. Carr; Andrew J. Borst; et al. (Proceedings of the National Academy of Sciences, 2025)
Clostridioides difficile remains a leading cause of hospital-acquired infections, with its primary virulence factor, toxin B (TcdB), responsible for severe colitis and recurrent disease. The closely related toxin, TcsL, from Paeniclostridium sordellii , causes a rarer but often fatal toxic shock syndrome, particularly in gynecological and obstetric contexts. We report the de novo design of small protein minibinders that directly neutralize TcdB and TcsL by preventing their entry into host cells. Using deep learning and Rosetta-based approaches, we generated high-affinity minibinders that protect cells from intoxication with picomolar potency and, in the case of TcsL, prolonged survival following lethal toxin challenge in mice. The designed proteins against TcdB demonstrate exceptional stability in proteolytic and acidic environments, making them well-suited for oral delivery—a valuable feature for treating C. difficile infections localized to the gastrointestinal tract. For TcsL, potent inhibitors were identified from 48 initial designs and 48 optimized designs, highlighting the potential of computational design for rapidly developing countermeasures against life-threatening bacterial toxins.